1,5-Bis(thiophen-2-yl)-3-(2,4,5-trimethoxyphenyl)pentane-1,5-dione - Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the title 1,5-diketone compound, C(22)H(22)O(5)S(2), the benzene ring makes dihedral angles of 41.51 (6) and 25.83 (6)° with the two thiophene rings, while the dihedral angle between the thiophene rings is 26.67 (7)°. An intramolecular C—H⋯O interaction generates an S(9) ring motif. In the crystal, molecules are linked into a three-dimensional network by weak C—H⋯O and C—H⋯π interactions, and a π–π interaction with a centroid–centroid distance of 3.6527 (8) Å.